Stories of Trouble and Troubled Stories: Narratives of Anti-German Sentiment from the Midwestern United States - Thompson, Maris (Narrative Works, 2015)
This article examines narratives of “trouble” from elderly second- and third- generation German American residents of Illinois. During the First and Second World Wars, many German American communities experienced targeted anti- German sentiment combined with government-sponsored efforts to eradicate the German language in schools, churches, and public spaces (Luebke, 1974; Tolzmann, 2001). Elderly narrators who tell stories about this time do so at considerable narrative risk, revealing both troubling memories and troubled tellings in the process. Troubled stories are difficult narrative terrain for these community members, and while they help complicate over-generalized portraits of German American assimilation, they present painful and often buried portraits of the past best forgotten in the minds of many. Despite their taboo nature, these stories of anti-German sentiment offer an important corollary to anti-immigrant feeling in the present day, especially in Midwestern regions that are experiencing heavy migration from newer immigrant communities.